The Sherwood Foresters of 1916: memories and memorials - Moran, James; Cullen, Fintan (Taylor & Francis, 2018)
This paper examines the memorialisation of the Sherwood Foresters who fought during the Easter Rising of 1916 in Dublin. These men, from Nottinghamshire and Derbyshire in the English midlands, suffered the greatest casualties of the British regiments involved in the insurrection, and participated in the firing squads that executed the rebel leaders. Yet the public and artistic memorialising of these English soldiers is not widely known, and this interdisciplinary paper seeks to tell the unfamiliar story of what happened to the Sherwood Foresters after the fighting of Easter Week ceased. We use archival material in order to explore how, at the time of the Rising, these men believed that they would be remembered. We examine the way that the Sherwood Foresters of Easter Week subsequently appeared in literature and drama. And we analyse the way that those soldiers have been commemorated in funerary memorials.